2007
DOI: 10.1007/s11121-007-0069-2
|View full text |Cite
|
Sign up to set email alerts
|

Community and Team Member Factors that Influence the Operations Phase of Local Prevention Teams: The PROSPER Project

Abstract: This study examined the longitudinal predictors of quality of functioning of community prevention teams during the "operations" phase of team development. The 14 community teams were involved in a randomized-trial of a university-community partnership project, PROSPER, that implements evidence-based interventions intended to support positive youth development and reduce early substance use, as well as other problem behaviors. The study included a multi-informant approach to measurement of constructs, and inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 30 publications
1
62
1
Order By: Relevance
“…Wave 1 pretest findings are reported elsewhere (e.g., Feinberg et al, 2007; Greenberg et al, 2007). Team data at organizational and operations phases (Waves 2 and 3) were collected 6 and 18 months after team formation, when team operations and program implementation were fully supported by university funds.…”
Section: Methodsmentioning
confidence: 80%
See 3 more Smart Citations
“…Wave 1 pretest findings are reported elsewhere (e.g., Feinberg et al, 2007; Greenberg et al, 2007). Team data at organizational and operations phases (Waves 2 and 3) were collected 6 and 18 months after team formation, when team operations and program implementation were fully supported by university funds.…”
Section: Methodsmentioning
confidence: 80%
“…We found that that greater community level poverty was negatively related to early team functioning (as measured by Global Team Functioning – see methods) and that greater perceived community readiness and positive team member prevention attitudes positively predicted the quality of team functioning 6 and 18 months after PROSPER began (Feinberg et al, 2007a; Greenberg, Feinberg, Meyer, Spoth, & Redmond, 2007). …”
Section: The Prosper Partnership Modelmentioning
confidence: 89%
See 2 more Smart Citations
“…Aarons, 2004). These scales were selected because they measure important influences on continued program use identified in the literature as described in the introduction (Hodge & Tuners, 2015), include key inner context factors measured at the practitioner (program) and team (organization) level (to match the theory), and have adequate to good internal consistency (Aarons, 2004;Feinberg, Chilenski, Greenberg, Spoth, & Redmond, 2007). They were originally developed to measure coalition functioning, and program appeal and requirement, respectively, as supports that influence EBP implementation and this study checks how they hang together when measuring continued implementation.…”
Section: Methodsmentioning
confidence: 99%